Eye diseases among drivers In the University College Hospital and College of Medicine, University of lbadan, Nigeria. (2009)
Objective of this study is to determine the pattern of eye diseases amongst drivers of College of Medicine, University of Ibadan (UI) and the University College Hospital (UCH) Ibadan. Cross sectional study of (99) drivers employed by the two institutions using a semi structured questionnaire and through eye examination at the eye clinic of UCH. Our results show that age range of respondents was from 39-60 years , mean 50.1+/- 4.78 years. Driving experience ranged from 5 to 43 years, mean 27.9years. +/- 6.24. Causes of ocular morbidity were pterygium 14.1 %, pingueculum 8 %, optic atrophy 8%, glaucoma 4%, and pathological myopia 1%. Risk of developing anterior segment disease increased with number of years spent driving. (OR2.4, 95% C! 1.1-6.2; P=O.05). We conclude that periodic eye examination of drivers can help to identify potential blinding eye diseases such as glaucoma and cataract and allow prompt treatment to prevent blindness and ensure safe driving. Drivers may be redeployed to an administrative job after a prolonged period of driving and when visual impairment ensures.